2017
DOI: 10.1111/imr.12578
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering interactions between the gut microbiota and the immune system via microbial cultivation and minimal microbiomes

Abstract: Summary The community of microorganisms in the mammalian gastrointestinal tract, referred to as the gut microbiota, influences host physiology and immunity. The last decade of microbiome research has provided significant advancements for the field and highlighted the importance of gut microbes to states of both health and disease. Novel molecular techniques have unraveled the tremendous diversity of intestinal symbionts that potentially influence the host, many proof-of-concept studies have demonstrated causat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 197 publications
(326 reference statements)
0
78
0
8
Order By: Relevance
“…An advantage of the latter method is the known composition of the microbiota, as emphasized above. A drawback, however, is formed by the risk that the desired phenotype (in this case a normalized host) cannot be entirely recapitulated (100).…”
Section: Bottom-up Versus Top-down Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of the latter method is the known composition of the microbiota, as emphasized above. A drawback, however, is formed by the risk that the desired phenotype (in this case a normalized host) cannot be entirely recapitulated (100).…”
Section: Bottom-up Versus Top-down Approachesmentioning
confidence: 99%
“…Nevertheless, due to the complexity of the immune system, it is difficult to quantify and compare the model hosts used with respect to immunological parameters. The key findings on the interactions of gut microbiota members and their products with the immune system have recently been reviewed elsewhere (100). Those authors emphasized the value of minimal microbiomes and subsequent standardized (animal) models.…”
Section: Host Parameters Influencing the Microbiotamentioning
confidence: 99%
“…Salmonella enterica, Escherichia coli, rotavirus, coronavirus Cryposporidium parvum) that can endanger the newborn (Cho and Yoon, 2014;Gomez and Weese 2017). However, there is increasing evidence that the colonization of the mammalian gastrointestinal tract plays a crucial role in the development of the mucosal immune system and influences the growth and performance of the individual (Schwarzer et al 2016;Clavel et al 2017). In summary, the evolution of the microbiota has great significance for the health of the newborn.…”
Section: Introductionmentioning
confidence: 99%
“…Recent culture‐independent next‐generation DNA sequencing (NGS) analysis of 16S rRNA genes has revealed that the guts of humans and other mammals contain trillions of bacterial cells, comprising 500–1000 different bacterial species. The importance of the gut microbiota to host health has been suggested in numerous studies (Clavel, Gomes‐Neto, Lagkouvardos, & Ramer‐Tait, ; Clavel, Lagkouvardos, & Steacher, ). In addition, the relationship between aging and the gut microbiota, which was proposed by Metchnikoff over a century ago (Cavaillon & Legout, ), and has been supported by the results of NGS analyses (Sánchez et al, ).…”
Section: Introductionmentioning
confidence: 97%